Ethnomedicinal Usage, Phytochemistry and Pharmacological Potential of Solanum surattense Burm. f. - Kamrul Hasan; Shabnam Sabiha; Nurul Islam; João F. Pinto; Olga Silva (MDPI AG, 2024)
Solanum surattense Burm. f. is a significant member of the Solanaceae family, and the Solanum genus is renowned for its traditional medicinal uses and bioactive potential. This systematic review adheres to PRISMA methodology, analyzing scientific publications between 1753 and 2023 from B-on, Google Scholar, PubMed, Science Direct, and Web of Science, aiming to provide comprehensive and updated information on the distribution, ethnomedicinal uses, chemical constituents, and pharmacological activities of S. surattense, highlighting its potential as a source of herbal drugs. Ethnomedicinally, this species is important to treat skin diseases, piles complications, and toothache. The fruit was found to be the most used part of this plant (25%), together with the whole plant (22%) used to treat different ailments, and its decoction was found to be the most preferable mode of herbal drug preparation. A total of 338 metabolites of various chemical classes were isolated from S. surattense, including 137 (40.53%) terpenoids, 56 (16.56%) phenol derivatives, and 52 (15.38%) lipids. Mixtures of different parts of this plant in water-ethanol have shown in vitro and/or in vivo antioxidant, anti-inflammatory, antimicrobial, anti-tumoral, hepatoprotective, and larvicidal activities. Among the metabolites, 51 were identified and biologically tested, presenting antioxidant, anti-inflammatory, and antitumoral as the most reported activities. Clinical trials in humans made with the whole plant extract showed its efficacy as an anti-asthmatic agent. Mostly steroidal alkaloids and triterpenoids, such as solamargine, solanidine, solasodine, solasonine, tomatidine, xanthosaponin A-B, dioscin, lupeol, and stigmasterol are biologically the most active metabolites with high potency that reflects the new and high potential of this species as a novel source of herbal medicines. More experimental studies and a deeper understanding of this plant must be conducted to ensure its use as a source of raw materials for pharmaceutical use.